Low birth weight and small for gestational age are associated with complications of childhood and adolescence obesity: Systematic review and meta‐analysis. (16th November 2021) - Martín‐Calvo, Nerea; Goni, Leticia; Tur, Josep A.; Martínez, J. Alfredo
Summary: In recent decades, the incidence of type 2 diabetes (T2D) has increased dramatically in children and adolescents, posing a real public health problem. Beyond unhealthy diets and sedentary lifestyles, growing evidence suggests that some perinatal factors, such as low birth weight (LBW), are associated with higher risk of T2D in adulthood. In this regard, it remains unclear whether the increased risk is already present in childhood and adolescence. We conducted a systematic review and meta‐analysis to clarify the association of LBW or being small for gestational age (SGA) with insulin resistance in childhood and adolescence. The systematic review resulted in 28 individual studies, and those with the same outcome were included within two random‐effects meta‐analyses. Compared with children or adolescents born with adequate size for gestational age, those SGA had 2.33‐fold higher risk of T2D (95% confidence interval [CI]: 1.05–5.17). Furthermore, LBW and being SGA were associated with 0.20 higher mean homeostasis model assessment of insulin resistance (HOMA‐IR) values (95% CI: 0.02–0.38). Given the high prevalence of preterm babies, from a population perspective, these results may be of great importance as they point to the existence of a potentially vulnerable subgroup of children and adolescents that could benefit from screening tests and early preventive strategies.